PRAANGGAPAN DALAM “ICH LIEBE DEUTSCH” DI FACEBOOK (PRESUPPOSITION OF “ICH LIEBE DEUTSCH” IN FACEBOOK) - Louisa Rina Moningka (Kadera Bahasa, 2016)
The study of presumption in Ich Liebe Deutsch in Facebook deals with how presumptions in speeches expressed in Ich Liebe Deutsch in Facebook. The study is conducted to gain description presumption based on the speeches by applying linguistic theory, especially, pragmatical approach that is hoped to be useful for readers in increasing vocabularies of Germans, and enhancing knowledge on Wendungen or German’s expressions as well as to get some descriptions of culture/lifestyle of the Germans. The method of descriptive qualitative in the study is done especially in dealing with the data, such as collecting, analyzing, and presenting the result (of the analysis). Speeches expressed in Ich Liebe Deutsch is updated information and they describe the life of German society from adolescents, adults, to those of the old age, and they relate to their daily lives. Those speeches are interesting, due to most of them and clear information of speeches that enable readers to get the message (of the speaker). Besides, there are speeches that need basic understanding on the culture of the language.